A hub and spoke network model to analyse the secondary dispersal of introduced marine species in Indonesia. (5th September 2014) - Azmi, Fauziah; Hewitt, Chad L.; Campbell, Marnie L.
Abstract: Indonesia is a biodiversity hotspot threatened with new introductions of marine species. As with many countries, Indonesia has a stratified shipping network of international ports linked to a large suite of domestic ports. We developed a hub and spoke network model to examine the risk associated with the secondary transfer of introduced marine species from the port hub of Tanjung Priok in Jakarta Bay to the 33 Indonesian provinces (including other ports in the Jakarta province). An 11-year shipping dataset was used (vessel next port of call records for maritime vessels that originated in Jakarta Bay and that remained in domestic waters) to derive a province ranking of vulnerability. Fifteen provinces represented almost 94% of the traffic frequency, with East Java and Jakarta provinces dominating. All urban provinces featured within the top seven highest frequency traffic provinces. Traffic patterns reflect an intra-coastal reliance on shipping, with traffic frequency decreasing with distance from Jakarta Bay. Provinces were regionalized into three categories (Lampung to East Java, Makassar Straits, and Malacca Straits) each with different vulnerabilities based on their values.